Gut microbiota and Parkinson’s disease: potential links and the role of fecal microbiota transplantation - Feng, Maosen; Zou, Zhiyan; Shou, Pingping; Peng, Wei; Liu, Mingxue; Li, Xiaoan (Frontiers in Aging Neuroscience, 2024)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide and seriously affects the quality of life of elderly patients. PD is characterized by the loss of dopaminergic neurons in the substantia nigra as well as abnormal accumulation of α-synuclein in neurons. Recent research has deepened our understanding of the gut microbiota, revealing that it participates in the pathological process of PD through the gut-brain axis, suggesting that the gut may be the source of PD. Therefore, studying the relationship between gut microbiota and PD is crucial for improving our understanding of the disease’s prevention, diagnosis, and treatment. In this review, we first describe the bidirectional regulation of the gut-brain axis by the gut microbiota and the mechanisms underlying the involvement of gut microbiota and their metabolites in PD. We then summarize the different species of gut microbiota found in patients with PD and their correlations with clinical symptoms. Finally, we review the most comprehensive animal and human studies on treating PD through fecal microbiota transplantation (FMT), discussing the challenges and considerations associated with this treatment approach.